Comparative characteristics of the mining industry of Ukraine and Greenland: main aspects and features (Economics and region, 2024)
The article examines the role of the manufacturing industry in the economies of Ukraine and Greenland, emphasizing its impact on economic growth, job creation, and infrastructure development. Ukraine has rich resources, in particular coal and iron ore, which provide domestic needs and exports. Greenland, on the other hand, shows potential due to its mineral and oil reserves, but faces environmental challenges and needs for infrastructure upgrades. Both countries face challenges such as the environmental impacts of extraction, which require adaptation of technologies and resource management strategies. The article also analyzes the research of Ukrainian and international scientists who investigate the effectiveness of resource management in the face of global challenges. Comparing the approaches of Ukraine and Greenland may reveal best practices for improving economic sustainability. The study focuses on the need to adapt to new conditions, particularly in the context of martial law in Ukraine, and aims to find out how countries cope with the consequences of the extractive industry. The paper highlights the importance of balancing economic benefits and environmental risks, highlighting the need for new management strategies to ensure long-term sustainability. The occupation of the Eastern part of Ukraine significantly affected the country's economy and its financial system, which led to large material losses due to the physical destruction of housing, infrastructure, as well as social and industrial facilities. The decrease in the volume of coal production negatively affected the energy security of Ukraine, a significant part of our thermal power plants (TPPs) was left without the necessary fuel. Damage to coal mining and transport infrastructure, as well as the closure and flooding of mines as a result of hostilities. The occupation has serious environmental consequences, such as water pollution and destruction of buildings. At the same time, global warming has opened up new opportunities for minerals in Greenland, sparking China's interest in controlling the region. However, the interests of Chinese investors turned out to be uncoordinated and limited, as the Chinese authorities do not put pressure on them to invest in ecology. China is also seeing the Arctic as an important new region for economic presence, which could lead to increased tensions with Denmark and the US. In addition to insufficient investment by the US and Denmark in Greenland, Chinese investment can be presented as an opportunity for economic development of the island, but at the same time raises fears in Denmark about the loss of control over natural resources. Greenland is trying to balance its desire for autonomy with Denmark's interests, while Ukraine faces geopolitical challenges due to its conflict with Russia. Both countries are developing mining industries, but have different challenges, including environmental, social and political. However, after the start of the war, new problems arose that required large capital investments and quick decision-making.
Keywords: extractive industry; Ukraine; Greenland; natural resources; ecology; investments; structural changes of the economy